1999
DOI: 10.1021/bi9911379
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Roles of Surface Histidyl Residues in the Molecular Basis of the Bohr Effect and of β143 Histidine in the Binding of 2,3-Bisphosphoglycerate in Human Normal Adult Hemoglobin

Abstract: Site-directed mutagenesis has been used to construct two mutant recombinant hemoglobins (rHbs), rHb(betaH116Q) and rHb(betaH143S). Purified rHbs were used to assign the C2 proton resonances of beta116His and beta143His and to resolve the ambiguous assignments made over the past years. In the present work, we have identified the C2 proton resonances of two surface histidyl residues of the beta chain, beta116His and beta143His, in both the carbonmonoxy and deoxy forms, by comparing the proton nuclear magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 45 publications
3
83
0
Order By: Relevance
“…Specifically, the golden-mantled ground squirrel, thirteenlined ground squirrel, Uinta chipmunk and least chipmunk share an unusual substitution at the C-terminus of the α-chain, α141Arg→Cys, and the major β-chain of the golden-mantled ground squirrel has an unusual substitution at the C-terminus, β146His→Gln (Fig.3). Both C-terminal residues are known to contribute to the pH sensitivity of Hb-O 2 binding (the Bohr effect) in human Hb (Perutz, 1970;Weber and Fago, 2004;Perutz, 1983;Berenbrink, 2006;Fang et al, 1999;Lukin and Ho, 2004). The golden-mantled ground squirrel also has a highly unusual substitution at another highly conserved β-chain position, β55Met→Ile (Fig.3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the golden-mantled ground squirrel, thirteenlined ground squirrel, Uinta chipmunk and least chipmunk share an unusual substitution at the C-terminus of the α-chain, α141Arg→Cys, and the major β-chain of the golden-mantled ground squirrel has an unusual substitution at the C-terminus, β146His→Gln (Fig.3). Both C-terminal residues are known to contribute to the pH sensitivity of Hb-O 2 binding (the Bohr effect) in human Hb (Perutz, 1970;Weber and Fago, 2004;Perutz, 1983;Berenbrink, 2006;Fang et al, 1999;Lukin and Ho, 2004). The golden-mantled ground squirrel also has a highly unusual substitution at another highly conserved β-chain position, β55Met→Ile (Fig.3).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the Bohr effect, studies of human HbA have demonstrated that H + ions mainly reduce Hb-O 2 affinity by protonating the α-amino termini and the C-terminal β146His, which stabilizes the deoxy T-state through the formation of additional salt bridges within and between subunits (Berenbrink, 2006;Fang et al, 1999;Lukin and Ho, 2004;Perutz, 1970;Perutz, 1983;Weber and Fago, 2004). The C-terminal α141Arg does not directly contribute to the Bohr effect [the pK a (acid dissociation constant) of Arg is 12.0, so it is overwhelmingly protonated at pH7.4], but it contributes indirectly to the Cl --dependent Bohr effect by facilitating the Cl --assisted charge stabilization of the free-NH 2 terminus of α1Val.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key examples of allosteric modulator characterization are the detailed studies on aspartic transcarbamylase and its feedback inhibition [4,5] . Other examples of allosteric actions involve non-enzymatic proteins such as the oxygen carrier hemoglobin, whose affinity is regulated by protons through the Bohr effect without involving binding to the O 2 site, or by 2,3-bisphosphoglycerate binding to an allosteric site on hemoglobin that affects O 2 trapping [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…According to the mechanism proposed by Perutz [2] , the cooperative effects arise from the equilibrium between two alternative quaternary states, the deoxy T (or low-affinity) state and the oxy R (or highaffinity) state. In addition to CO 2 , Cl − , and HPO 4 2− , the concentrations of 2,3-biphosphoglycerate (2,3-BPG) will affect the oxygen affinity [3][4][5][6][7] . 2,3-BPG is a small, highly anionic organic phosphate synthesized in red blood cells (RBCs).…”
Section: Introductionmentioning
confidence: 99%